From Fidelity to History : Film Adaptations as Cultural Events in the Twentieth Century. - Scholz, Anne-Marie (Transatlantic perspectives., 2013)
Scholarly approaches to the relationship between literature and film, ranging from the traditional focus upon fidelity to more recent issues of intertextuality, all contain a significant blind spot: a lack of theoretical and methodological attention to adaptation as an historical and transnational phenomenon. This book argues for a historically informed approach to American popular culture that reconfigures the classically defined adaptation phenomenon as a form of transnational reception. Focusing on several case studies- including the films Sense and Sensibility (1995) and Th.